Parents Strategies In Fostering Interest In Reading Al-Qur'an In Early Childhood At TPQ Masyithoh - Ainun Nur Rohma; Ainun Nadlif (Institut Agama Islam An-Nawawi Purworejo, 2023)
In general, learning the Qur'an is an important thing that must be instilled from an early age, so the right strategy is also needed to introduce it. Nowadays most parents neglect the provision of al qur'an education to children as a provision for their lives. Among them, parents are busy and do not care about children's Qur'an education, as a result many teenage children still cannot read the Qur'an, even though the Qur'an must be introduced from an early age. Therefore, parents must be able to foster children's interest in reading the Qur'an. Parents must be able to have creative strategies that can foster children's interest in reading the Qur'an to increase. The purpose of the study was to find out what are the factors that influence children's interest in reading the Qur'an and how parents' strategies in fostering interest in reading the Qur'an in early childhood. This research uses qualitative methods, with the research subjects being parents and teachers to get information about how parents' strategies in fostering children's interest in reading the Qur'an at an early age in the Alqur'an Education Park at Masyithoh Ngoro. Data collection techniques using observation, interviews, and documentation, while the stages of data analysis are data collection, data reduction, data presentation and conclusion of research results. The results showed that interest in reading the Qur'an arises because there are influencing factors, one of which is internal factors including talents and interests that are already owned and external factors including family, friends, and the surrounding environment. Parents' strategies in fostering interest in reading the Qur'an at tpq masyithoh are very diverse, namely parents as role models, as motivators, including children in TPQ / TPA, by habituation, using various media as supporting materials, using gadgets and the most important thing is spiritual support.